A germline JAK2 exon12 mutation and a late somatic CALR mutation in a patient with essential thrombocythemia - Hao, Zhuanghui; Li, Juan; Gao, Feng; Ren, Weixiao; Lu, Xiaomei; Feng, Jinyi; Zhang, Chen; Bian, Sicheng; Xie, Juan; Luo, Ming; Chang, Jianmei; Yang, Wanfang; et al. (Frontiers in Oncology, 2024)
Background It has been discovered that Janus kinase 2 (JAK2) exon12 mutations lead to the polycythemia vera (PV) phenotype, while somatic mutations of calreticulin (CALR) are associated with essential thrombocythemia (ET) or primary myelofibrosis. In this article, we report a case of ET with coexistence of JAK2 exon12 and CALR mutations. The objective of this study was to elucidate the pathogenicity mechanism of a JAK2 exon12 mutation (JAK2N533S) and the role of the coexistence of mutations on the hematological phenotype. Methods We designed a colony analysis of tumor cells obtained from this patient, and attempted to identify mutant genes using DNA from hair follicles. Mutation impairment prediction and conservative analysis were conducted to predict the mutation impairment and structure of JAK2N533S. In addition, we conducted a functional analysis of JAK2N533S by constructing Ba/F3 cell models. Results Three distinct tumor subclones, namely JAK2N533Shet+/CALRtype1het+, JAK2N533Shet+/CALRwt, and JAK2N533Shet+/CALRtype1hom+, were identified from the 17 selected erythroid and 21 selected granulocyte colonies. The analysis of hair follicles yielded positive results for JAK2N533S. According to the bioinformatics analysis, JAK2N533S may exert only a minor effect on protein function. Functional studies showed that JAK2N533S did not have a significant effect on the proliferation of Ba/F3 cells in the absence of interleukin-3 (IL-3), similar to wild-type JAK2. Notably, there were no increased phosphorylation levels of JAK2-downstream signaling proteins, including signal transducer and activator of transcription 3 (STAT3) and STAT5, in Ba/F3 cells harboring the JAK2N533S. Conclusion Our study revealed that the JAK2N533Shet+/CALRtype1het+ subclone was linked to a significant expansion advantage in this patient, indicating that it may contribute to the development of the ET phenotype. We further demonstrated that JAK2N533S, as a noncanonical JAK2 exon12 mutation, is a germline mutation that may not exert an effect on cell proliferation and protein function. These results and the present body of available data imply that certain noncanonical JAK2 mutations are not gain-of-function mutations leading to the development of myeloproliferative neoplasms.